"I am from nowhere": identity and self-perceived health status of skilled immigrants employed in low-skilled service sector jobs. Issue 2 (12th June 2017) - Subedi, Rajendra Prasad; Rosenberg, Mark Warren
Abstract : Purpose: The foreign-born skilled immigrant population is growing rapidly in Canada but finding a job that utilizes immigrants' skills, knowledge and experience is challenging for them. The purpose of this paper is to understand the self-perceived health and social status of skilled immigrants who were working in low-skilled jobs in the service sector in Ottawa, Canada. Design/methodology/approach: In this qualitative study, semi-structured interviews with 19 high-skilled immigrants working as taxi drivers and convenience store workers in the city of Ottawa, Canada were analysed using a grounded theory approach. Findings: Five major themes emerged from the data: high expectations but low achievements; credential devaluation, deskilling and wasted skills; discrimination and loss of identity; lifestyle change and poor health behaviour; and poor mental and physical health status. Social implications: The study demonstrates the knowledge between what skilled immigrants expect when they arrive in Canada and the reality of finding meaningful employment in a country where international credentials are less likely to be recognized. The study therefore contributes to immigration policy reform which would reduce barriers to meaningful employment among immigrants reducing the impacts on health resulting from employment in low-skilled jobs. Originality/value: This study provides unique insights into the experience and perceptions of skilled immigrants working in low-skilled jobs. It also sheds light on the "healthy worker effect" hypothesis which is a highly discussed and debated issue in the occupational health literature.